Assessing rainfall patterns and trend distribution in the Kelantan and Klang River Basin, Malaysia - Kamarulakmal, Muhammad Afiq Alif; Hashim, Rohasliney (Malaysian Institute Of Planners, 2025)
This study examined rainfall patterns and trends in the Kelantan and Klang River Basin in Malaysia over a ten-year period from 2010 to 2020. The analysis revealed that the Kelantan River Basin experienced an upward trend in rainfall during the Southwest Monsoon season, indicating a gradual increase in precipitation levels over the years. On the other hand, the Klang River Basin showed a relatively stable rainfall pattern without a significant trend observed. The study employed an independent t-test to compare the mean yearly rainfall between the two basins, with the findings showing no significant difference in overall precipitation levels (t(22) = -0.8, p = 0.07). However, the timing and duration of rainy seasons varied between the two basins. The Kelantan River Basin experienced a rainfall pattern that is aligned with the regular monsoon season. In contrast, the Klang River Basin displayed a notable gap in rainfall during a later month in the monsoon season. Moreover, the analysis considered the spatial variability of precipitation patterns within each basin. Specific stations in the Kelantan River Basin showed a positive trend in rainfall during the monsoon seasons (March, p = 0.013), whereas stations along the Klang River exhibited a declining trend (August, p = 0.119). These findings emphasize the influence of geographical locations, local climate conditions, and topographical features on rainfall distribution within the same country. In conclusion, this research highlights the need for further investigation into the factors driving these patterns, emphasizing the importance of effective water resource management and climate adaptation strategies in these basins to mitigate the impact of climate change.